2017
DOI: 10.1177/1533034617723754
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circulating Long Noncoding RNA HOTAIR as a Novel Biomarker for Diagnosis and Monitoring of Non–Small Cell Lung Cancer

Abstract: Long noncoding RNA (LncRNA) homeotic genes (HOX) transcript antisense RNA (HOTAIR) has been reported to play a vital role in various cancers. It has been found that HOTAIR was upregulated in non–small cell lung cancer (NSCLC) and involved in cell invasion and metastasis. The aberrant expression of HOTAIR is expected to serve as a potential biomarker for patients with NSCLC. Our aim in this study was to detect the plasma levels of HOTAIR and further evaluate its diagnostic value for NSCLC. The levels of HOTAIR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 34 publications
2
47
0
Order By: Relevance
“…However, the diagnostic performance of different lncRNAs in different studies is diverse. For instance, the sensitivity and specificity of PCAT6 was 87.7% and 97.4%, respectively,16 while of HOTAIR was 76.2% and 71.9%, respectively 17. The sensitivity and specificity of MALAT1 in Wen et al ’s study was 58.3% and 81.7%, respectively,18 while in Shi et al ’s research it was 87.5% and 94.1%, respectively 19…”
Section: Introductionmentioning
confidence: 86%
“…However, the diagnostic performance of different lncRNAs in different studies is diverse. For instance, the sensitivity and specificity of PCAT6 was 87.7% and 97.4%, respectively,16 while of HOTAIR was 76.2% and 71.9%, respectively 17. The sensitivity and specificity of MALAT1 in Wen et al ’s study was 58.3% and 81.7%, respectively,18 while in Shi et al ’s research it was 87.5% and 94.1%, respectively 19…”
Section: Introductionmentioning
confidence: 86%
“…HOTAIR also interacted with the chromatin remodeling factor LSH, which prompted LSH binding to the promoter of FOXA1; this occurrence suggests that HOTAIR mediated in the regulation of the FOXA1-to-FOXA2 ratio, resulting in migration and invasion in lung adenocarcinoma cancer (LAD) [28]. In addition, plasma HOTAIR levels were shown to be higher in patients with NSCLC than in healthy controls and were associated with histology subtypes and tumor-node-metastasis stages; this finding suggests that HOTAIR exhibits potential as a biomarker for diagnosing and monitoring patients with NSCLC [29]. One study observed that cigarette smoke extract (CSE) stimulated HOTAIR expression and that cytokine interleukin-6 increased HOTAIR expression via a signal transducer and activator of transcription 3 (Stat3) signaling, which contributed to epithelial-mesenchymal transition (EMT) and formation of cancer stem cells (CSCs) induced by CSE.…”
Section: Hotair In Lung Cancermentioning
confidence: 96%
“…In addition, many studies have highlighted that some lncRNA steadily subsist in human serum/plasma (Qi et al ., ; Shi et al ., ), facilitating subsequent investigation on the role of serum/plasma lncRNA in the diagnosis and prognosis of NSCLC. However, only few serum lncRNA, such as MALAT1, HOTAIR, and GAS5, exhibit significantly different serum expression levels between NSCLC patients and healthy controls (Li et al ., ; Liang et al ., ; Zhang et al ., ). Moreover, technical issues, such as using single or undercounted lncRNA, an insufficient specimen size, and a lack of independent validation, are often noted in such studies.…”
Section: Introductionmentioning
confidence: 99%